“Nothing is funnier than suffering”. Sport as a comic and perverse aesthetic practice - Andrew Harvey (Sport, Ethics and Philosophy, 2023)
The article takes up diverse strands of psychoanalytic thinking to investigate how desire is manifested in male team sporting environments. In particular, it is posited that sporting desire shares a remarkable structural similarity to the joking relationship in that they both work through the overcoming of obstacles. In doing so unconscious desires are long-circuited and only emerge in radically altered form, upending traditional gender and sexual subjectivities in the process. The paper explores the concept of desire from perspectives that are either straightforwardly psychoanalytic or heavily influenced by psychoanalytic thought. Initially, I examine desire from a Freudian viewpoint before looking at how Jacques Lacan extended Freudian analysis through a linguistic lens. I then explore desire in terms developed by Gilles Deleuze before turning, in the second part of the paper, to an examination of the work of George Bataille to consider the desire of sport through the mechanism of the joke to trace the complex routing that it often takes.